Tính đạo hàm của hàm số sau: $y = \frac{{a{x^2} + bx + c}}{{a’x + b’}},{\rm{ }}aa’ \ne 0$ .

Tính đạo hàm của hàm số sau: $y = \frac{{a{x^2} + bx + c}}{{a’x + b’}},{\rm{ }}aa’ \ne 0$ .

A. $ = \frac{{aa'{x^2} + 2ab’x + bb’ – a’c}}{{(a’x + b’)}}$

B. $ = \frac{{aa'{x^2} + 2ab’x + bb’ – a’c}}{{{{(a’x + b’)}^2}}}$

C. $ = \frac{{aa'{x^2} – 2ab’x + bb’ – a’c}}{{{{(a’x + b’)}^2}}}$

D. $ = \frac{{aa'{x^2} + 2ab’x – bb’ – a’c}}{{{{(a’x + b’)}^2}}}$

Hướng dẫn giải

Chọn D.
Ta có: $y’ = \frac{{(2ax + b)(a’x + b’) – a'(a{x^2} + bx + c)}}{{{{(a’x + b’)}^2}}}$
$ = \frac{{aa'{x^2} + 2ab’x + bb’ – a’c}}{{{{(a’x + b’)}^2}}}$ .